Syphilis: clinical and oral manifestations (Research, Society and Development, 2022)
The present study aims to analyze and understand the characteristics of oral manifestations caused by syphilis and highlight the importance of oral examination in order to obtain an adequate diagnosis and consequently a better prognosis. It consists of a narrative review of the literature that was carried out on the subject of syphilis and its oral manifestations, in which scientific articles were used that were found in databases such as SciELO and the Virtual Health Library (VHL) and those that were most relevant about of the purpose of the review. Syphilis is a curable, sexually transmitted infection caused by Treponema pallidum, which is a facultative gram-negative bacterium of the spirochete group. Its transmission occurs horizontally through sexual contact or vertically during pregnancy. From the literature review, it was possible to conclude that the oral manifestations of syphilis can present themselves in different ways, varying according to the stage of the disease. The dentist must always be aware of lesions suggestive of syphilis, as it’s oral manifestations are of paramount importance for a correct diagnosis.